Yritystukien tarjonta, täydentävyys ja toistuvuus - Heli Koski; Mika Pajarinen (The Research Institute of the Finnish Economy (ETLA), 2010)
We use the databases of Statistics Finland to explore the supply of public support for firms in Finland during the years 2000-2008. Particularly, this report provides a descriptive analysis of complementarities and repetitiousness of public support from the perspective of the applying firms. We observe that both the order of magnitude of public resources allocated annually for supporting firms and the number of firms applying for and receiving public support have increased during sample years. The relative financing shares of the organizations allocating support have remained relatively constant. We find that the probability to apply for and to receive public support increases with firm size, age and R&D intensity. The data also show that there are complementarities between certain support forms and organizations allocating public support and that various firms tend to receive support from the Finnish government repeatedly over time.
Keywords: H81; L53; O25; Y10; 330; Public support; public finance; industrial policy; Finland; Wirtschaftsförderung; Öffentliche Kreditvergabe; Subvention; Finnland